ARTISTIC INTERPRETATION OF UZBEK HISTORICAL MONUMENTS: BALANCING CREATIVITY AND CULTURAL HERITAGE - Madaliyeva Rushana Farhod qizi (FANLARARO TAFAKKUR MAVZUSIDAGI ILMIY-AMALIY KONFERENSIYA, 2026)
This article explores the role of contemporary Uzbek painters in interpreting historical monuments through visual art. The study focuses on techniques such as composition, color, perspective, symbolism, and human integration, highlighting how these methods preserve cultural heritage while promoting creative expression. The educational implications for art students, including the development of observation, spatial reasoning, and cultural literacy, are also discussed.